Synthesis Of Choline Chloride-acetic Acid Based Deep Eutectic Solvent (Des) For The Extraction Of Bioactive Polysaccharide From Garcinia Atroviridis Fruit - Razak, Nur Qistina Abdul (2024)
The fruit of Garcinia atroviridis was identified as a potential source of bioactive polysaccharides. This study explored the ability of these polysaccharides (referred to as GAP) to inhibit pancreatic lipase and angiotensin-converting enzyme (ACE), both of which are important in managing obesity and hypertension. The extraction of GAP was optimized using a microwave-assisted process involving deep eutectic solvents (DES). The study was promoted to prepare deep eutectic solvents (DES) from choline chloride and acetic acid in 1:2, 1:3, 1:4. The physicochemical properties of the resulting DES were fully characterized. The interaction of the DES components by hydrogen bonds was confirmed using Fourier-transform infrared spectroscopy (FTIR) and changes in wavenumbers of their functional groups. Moreover, these DES were shown to be hydrophilic and could dissolve in water with high polarity while having compatibility with many of semi-polar solvents. the DES demonstrates excellent potential for extraction applications due to its low pH and polar nature. Therefore, DES is a promising medium for extracting GAP. The yield of GAP was then extracted and the result concluded that the experimental yield of GAP (24.33%) closely matched the predicted yield (24.88%), confirming the accuracy of the extraction model. GAP was found to have a high molecular weight (28.15 ± 3.17 kDa) and viscosity (3.171 ± 1.23 Pa·s), along with a significant branching size (6.39 ± 0.030). These characteristics suggest that GAP can form complex structures that effectively inhibit enzyme activity by physically blocking the enzymes from accessing their substrates, thereby slowing down their function. In laboratory tests, GAP demonstrated significant inhibitory effects, reducing pancreatic lipase activity by 79.41% and ACE activity by 81.23%. These results indicate that GAP has strong potential for use in developing anti-obesity and antihypertensive treatments. Further optimization of GAP's bioactivity led to even better results, with optimized GAP inhibiting pancreatic lipase (GAP-L) by 87.93% and GAP that inhibits ACE (GAP-A) by 95.91%. The experimental values closely aligned with the predicted values (86.57% for pancreatic lipase inhibition and 95.64% for ACE inhibition), further validating the model. Therefore, GAP shows great promise as a potential source for developing effective agents to manage obesity and hypertension. The suitability of the DES produced as well shown to have a polar nature, making it capable of interacting with and dissolving a wide range of polar compounds, including polysaccharides and other bioactive molecules.